Adapting agriculture to climate change: a global initiative to collect, conserve, and use crop wild relatives - Dempewolf, Hannes; Eastwood, Ruth J.; Guarino, Luigi; Khoury, Colin K.; Muller, JV; Toll, Jane (Informa UK Limited, 2014)
The main objective of the“Adapting Agriculture to Climate Change” project is to collect and protect the genetic diversity of a portfolio of plants with the characteristics required for adapting the world's most important food crops to climate change. The initiative also aims to make available this diversity in a form that plant breeders can readily use to produce varieties adapted to the new climatic conditions that farmers, particularly in the developing world, are already encountering. Such adaptation is a key component of securing the world's future food production. This paper serves to inform interested researchers of this important initiative and encourage collaboration under its umbrella.